The layered reality of sustainable transport campaigning - Kiviluoto, Katariina (My University, 2017)
This Master’s thesis examines sustainable traffic through the lenses of sustainable traffic campaigners. Sustainable traffic campaigning is a relatively new research topic while campaigners have not really been researched at all. However, this topic is relevant as traffic emission targets set by the EU demand action, and the share of sustainable traffic modes should be increased. Both hard and soft measures are required if these targets are to be met. Soft measures, usually coined under the term mobility management, tend to include some form of traffic campaigning. As campaigning is generally accepted as a relevant means to encourage behaviour change, sustainable traffic campaigners can be regarded as key actors in getting people to voluntarily embrace more sustainable transport practices. Successful campaigns may challenge people to consider their transport habits and practices but they might also create some momentum for lasting lifestyle changes. This thesis relies on qualitative research and futures studies as its main theoretical frameworks. The objective has been to examine how worldviews and other underlying structures the campaigners have frame the way campaigns are designed and executed. Research material has been gathered by interviewing people who actively work with sustainable traffic campaigns. The research material has then been analysed with Causal Layered Analysis (CLA), a post-structuralist method developed by the futurist Sohail Inayatullah. CLA depicts the world through 4 layers all of which are instrumental to comprise a profound view of any issue under examination. The analysis requires the researcher to move vertically and horizontally in a constant dialogue between research material, different layers and research literature in order to examine underlying systemic structures, worldview related framings and unconscious myths lurking in the background. All of these underlying aspects may affect the way campaigns are either consciously or unconsciously designed and executed. In addition, 4 futures images have been formed as a natural continuum of the CLA-analysis. These images offer a glimpse on what may lie ahead for transport campaigning in 2030. It can be argued based on the analysis that systemic constraints, worldviews and certain mythical tropes may influence the way campaigns are designed and carried out. They may affect, for example which target groups are mainly chosen and which methods are used. They may thus even influence the results likely to be achieved with campaigns. However, the 4 futures images surfacing from the analysis offer some assurance that other alternative means and methods are available which could be added to campaign toolkits to create even more effective campaigns. These might encourage people to change their transport behaviour and even increase the chances of profound lifestyle changes.